Analysis of Parental Satisfaction with Education Services in Private Elementary Schools - Mashrul, Nenden Nadya Rizky; Widowati, Saras Pangestu Sri; Ferdiansah, Renaldi; Sholeh, Slamet (CV. Rayyan Dwi Bharata, 2024)
Analysis of the quality of educational services is based on the level of satisfaction of education service users with the services provided by educational institutions, namely schools. This research aims to understand the public's perception, particularly students and their parents, of the quality of basic education services. Nowadays, competition in the education sector is very evident in society, including at the basic education level. This is reflected in the high enthusiasm of parents to enroll their children in schools with the best quality. Consequently, many new schools, especially private ones, have emerged, including integrated elementary schools and madrasah ibtidaiyah. The demand for high-quality education is very significant in today's life. Schools strive to provide the best services to remain competitive and be the choice of the community. The quality of educational services has a significant impact on parents' satisfaction. There are five dimensions of parents' satisfaction with the quality of educational services: the tangible dimension, the reliability dimension, the responsiveness dimension, the assurance dimension, and the empathy/caring dimension. Customers will feel dissatisfied if the outcomes do not meet their expectations. Customer dissatisfaction with the services provided by a school is believed to be one of the factors that cause a decline in the number of students, which is certainly detrimental to the school. Conversely, if customers are satisfied with the services provided by the school, they will continue to use the educational services and give positive feedback to others about the educational institution.